2015
DOI: 10.1089/tmj.2014.0048
|View full text |Cite
|
Sign up to set email alerts
|

Including Men in Prenatal Health: The Potential of e-Health to Improve Birth Outcomes

Abstract: This study explored the role men play in prenatal health, a promising avenue toward better birth outcomes. Using e-health is an opportune approach-it can reach men unavailable to attend prenatal programs because of work or feeling unwelcome at programs deemed "only for women."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Some researchers delivered the intervention at the group level, 35 -40, 48, 55 couple level, 43,49,52 or individual level. 10,42,45,46 Studies also differed in whether researchers used a manualized curriculum, who delivered the sessions (eg, nurse versus social worker), when the sessions were delivered (eg, before birth versus after birth), and mode of intervention delivery (eg, in-person versus mobile application) (for details see Table 2). Of the 21 studies, only 4 were categorized as low RoB (ie, scoring 3 or higher) and 17 high RoB (ie, scoring 2 or less) as shown in Table 4.…”
Section: Assessment Of Robmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers delivered the intervention at the group level, 35 -40, 48, 55 couple level, 43,49,52 or individual level. 10,42,45,46 Studies also differed in whether researchers used a manualized curriculum, who delivered the sessions (eg, nurse versus social worker), when the sessions were delivered (eg, before birth versus after birth), and mode of intervention delivery (eg, in-person versus mobile application) (for details see Table 2). Of the 21 studies, only 4 were categorized as low RoB (ie, scoring 3 or higher) and 17 high RoB (ie, scoring 2 or less) as shown in Table 4.…”
Section: Assessment Of Robmentioning
confidence: 99%
“…Mode of delivery seems to have included both video and in-person sessions. Mackert et al, 45 2015 My Pregnancy Today…”
Section: Father Involvementmentioning
confidence: 99%
“…The findings of this particular study answer a call for how to positively engage men in pregnancy health -moving beyond traditional interventions that only target women [18,19]. A preliminary investigation demonstrated the potential of using eHealth to engage men in this issue, and a subsequent study built on that with targeted content developed specifically for men [13,20]. The findings of this national survey confirm this is an effective way to expose men to this important content.…”
mentioning
confidence: 54%
“…These are some of the difficulties that need to be overcome to ensure the partner's involvement of the PNC [23,46]. Similar studies have shown that health communication technologies had a good acceptance and the messages were considered useful as a form of support for the new fathers and they attract men to a closer experience in the care and support of their partner during the pregnancy [26,47]. Our results show good acceptability of this program, a little more than half of the partners participated, comparing to data of partner's participation in PNC from the local SUS which in 2014 was 37% [44].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO defines eHealth as the use of information and communication technologies for health, also found in the literature as telemedicine, SMS and mHealth [24]. The use of the technological resources of communication in health is a promising, innovative field and is being widely studied, due to being strategies that arouse curiosity and generate greater adherence in men [25,26].…”
Section: Introductionmentioning
confidence: 99%